Annual Report on Exchange Arrangements and Exchange Restrictions 1987. (Annual Report on Exchange Arrangements and Exchange Restrictions; 1987, 1987)
This report discusses developments in the international exchange rate and restrictive systems. The period covered by this report is 1986 and, for major developments, the first quarter of 1987. The report highlights that in 1986, protectionist pressures for trade restrictions in the industrial countries continued to be fueled by large and widening bilateral trade imbalances, persistently high levels of unemployment, and a widespread slowing of economic growth. In spite of continued resistance by some governments, quantitative restrictions were tightened in many industrial countries. There were nevertheless several positive developments in the trade and exchange system.